(untitled) (Perner’s Contacts, 2020)
The paper focuses on intermodal transportation systems for semitrailers in Europe. Transportation of semitrailers by rail is a good alternative to direct road transport. In the paper, individual systems are presented and their characteristics are explained. The characteristics of individual transportation systems are the inputs into the WSA and the TOPSIS methods. The results of the methods answers the question which semitrailer transportation system is the most suitable (beneficial) for trucking companies today. The paper may be a source of information for state authorities, trucking companies, intermodal transportation operators and terminal operators.